(3GdBKGQ GdLdjIs - (3GdYeQj, GdehUdj, GdMfaj , GdNWjH, jGSjf Hf NjQ Gddg Hf eMehO Hf ehSi, J HYO (B1232 (3g`s ((3eMeO UGdM Hf YHO Gddgs)
(3ChdgG (B:s
(3eHJhQ GdChd, hChd GdehLhO efg bhdg(B: (3hGNJai CjGeG Ke XaQhG Hg abHVhg hbJdhg(B...s
(3BNQgG (B:s
...(3hgQH hbOe Edi GdehUd hgh CYei Ke JhLg Edi ESdGeHhd(B.s
(3JHUQI GdYfhGf (B:s
(3GdGKGQ GdLdjI aj GdMhGOK GdGQVjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B4(3,U(B81s
(3GdCYdGe(B:(3L(B8(3,U(B129s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs